Putting a price on drugs: an economic sociological study of price formation in illegal drug markets - Møller, Kim (Criminology, 2019)
Prices in illegal drug markets are difficult to predict. Based on qualitative interviews with 68 incarcerated drug dealers in Norway, we explore dealers’ perspectives on fair prices and the processes that influence their pricing decisions. Synthesized through economic sociology, we draw on perspectives from traditions as different as behavioral economics and cultural analysis to demonstrate how participants in illicit drug distribution base their pricing decisions on institutional context, social networks, and drug market cultures. We find that dealers take institutional constraints into consideration and search for niches with high earnings and low risks. The use of transactions embedded in social networks promotes a trusting form of governance, which enables strategic network management and expedient distribution but also uncompetitive pricing. Finally, dealers’ pricing decisions are embedded in three different cultures narratives: business, friendship, and street cultural stories, with widely varying implications for prices. Our findings demonstrate how an economic sociology of illicit drug distribution can extend insights from behavioral economics and cultural studies into a coherent criminology of illegal drug markets.